Renovación urbana y actividad económica - Cano Hurtado, Juan Jaime; Blasco Sánchez, María Del Carmen; Martínez Pérez, Francisco Juan; Gascón Hernández, Ana Mª; Esteve Aguado, Carlos (Universitat Politècnica de València Editorial, 2022)
Published